Effects of Multidimensional Self-Esteems on Health Promotion Behaviors in Adolescents - Liu, Bin; Tian, Lu; Yang, Shuo; Wang, XueQiang; Luo, Jiong (Frontiers in Public Health, 2022)
Objective To explore the relationships between multidimensional self-esteems and health behaviors among adolescents by demographic background factors, so as to provide an important reference for the intervention of health promotion behavior and self-esteem education in the future. Methods Taking adolescents in Chongqing as the object, this paper investigates the students in 24 primary and secondary schools (half of health promotion schools and half of non-promotion schools) by means of Stratified random sampling, and Using SPSS 21.0 and AMOS 19.0 statistical analysis software to process the collected data. Results 1) gender and age significantly affected adolescents' self-esteem and health promotion behavior, which showed that boys's perception of self-esteem was lower than that of girls, while girls were more likely to implement health promotion behavior than boys; 2) Children from two parent families or families with higher parental education are more able to implement health promotion behavior and enjoy higher self-esteem, while family economic status has no effect on adolescents' self-esteem and health promotion behavior; 3) Compared with students in ordinary schools, adolescents in health promotion schools (HPS) have higher self-esteem and can implement health promotion behavior more; 4) The higher the self-esteem of adolescents, the better their health promotion behavior; The higher the sense of interpersonal ability, the more able to implement social support behavior; The higher the sense of physical ability and physiological value, the more able to implement sports behavior; The higher the sense of academic ability, the more able to implement nutritional behavior; The higher the external recognition and physiological value, the better the performance of nutritional behavior and stress management; The higher the internal evaluation, the more able to implement health responsibility and exercise behavior. Conclusion Socio-economic background can indeed have a direct or indirect impact on adolescent health promotion behavior, and multidimensional self-esteem can explain about 70% of the variation of health promotion behavior, which seems to suggest that improving adolescent self-esteem is the focus of health promotion and health education in the future.